(untitled) (Swiss Medical Weekly, 2012)
In population surveys of the exposure to medical X-rays both the frequency of examinations and the effective dose per examination are required. The use of the Swiss medical tariffication system (TARMED) for establishing the frequency of X-ray medical examinations was explored. The method was tested for radiography examinations performed in 2008 at the Lausanne University Hospital. The annual numbers of radiographies determined from the “TARMED” database are in good agreement with the figures extracted from the local RIS (Radiology Information System). The “TARMED” is a reliable and fast method for establishing the frequency of radiography examination, if we respect the context in which the “TARMED” code is used. In addition, this billing context provides most valuable information on the average number of radiographs per examination as well as the age and sex distributions. Radiographies represent the major part of X-ray examinations and are performed by about 4,000 practices and hospitals in Switzerland. Therefore this method has the potential to drastically simplify the organisation of nationwide surveys. There are still some difficulties to overcome if the method is to be used to assess the frequency of computed tomography or fluoroscopy examinations; procedures that deliver most of the radiation dose to the population. This is due to the poor specificity of “TARMED” codes concerning these modalities. However, the use of CT and fluoroscopy installations is easier to monitor using conventional survey methods since there are fewer centres. Ways to overcome the “TARMED” limitations for these two modalities are still being explored.